The EpiOcular Eye Irritation Test (EIT) for Hazard Identification and Labelling of Eye Irritating Chemicals: Protocol Optimisation for Solid Materials and the Results after Extended Shipment. Issue 2 (May 2015) - Kaluzhny, Yulia; Kandárová, Helena; Handa, Yuki; DeLuca, Jane; Truong, Thoa; Hunter, Amy; Kearney, Paul; d'Argembeau-Thornton, Laurence; Klausner, Mitchell
The 7th Amendment to the EU Cosmetics Directive and the EU REACH Regulation have reinforced the need for in vitro ocular test methods. Validated in vitro ocular toxicity tests that can predict the human response to chemicals, cosmetics and other consumer products are required for the safety assessment of materials that intentionally, or inadvertently, come into contact with the eye. The EpiOcular Eye Irritation Test (EIT), which uses the normal human cell-based EpiOcular™ tissue model, was developed to address this need. The EpiOcular-EIT is able to discriminate, with high sensitivity and accuracy, between ocular irritant/corrosive materials and those that require no labelling. Although the original EpiOcular-EIT protocol was successfully pre-validated in an international, multicentre study sponsored by COLIPA (the predecessor to Cosmetics Europe), data from two larger studies (the EURL ECVAM–COLIPA validation study and an independent in-house validation at BASF SE) resulted in a sensitivity for the protocol for solids that was below the acceptance criteria set by the Validation Management Group (VMG) for eye irritation, and indicated the need for improvement of the assay's sensitivity for solids. By increasing the exposure time for solid materials from 90 minutes to 6 hours, the optimised EpiOcular-EIT protocol achieved 100% sensitivity, 68.4% specificity and 84.6% accuracy, thereby meeting all the acceptance criteria set by the VMG. In addition, to satisfy the needs of Japan and the Pacific region, the EpiOcular-EIT method was evaluated for its performance after extended shipment and storage of the tissues (4–5 days), and it was confirmed that the assay performs with similar levels of sensitivity, specificity and reproducibility in these circumstances.